Effects of silica powder and cement type on durability of ultra high performance concrete (UHPC). (February 2016) - Alkaysi, Mo; El-Tawil, Sherif; Liu, Zhichao; Hansen, Will
Abstract: Ultra-high performance concrete (UHPC) achieves extraordinary strength characteristics through optimization of the particle packing density of the cementitious matrix. The dense matrix also promotes exceptional durability properties and is arguably the biggest benefit of the material. A durable concrete enables structures to last longer, reduces the cost of maintenance and helps achieve a significantly more sustainable infrastructure. To assess the durability of UHPC, the performance of several non-proprietary blends are investigated by assessing the materials' resistance to freeze-thaw cycles, ingress of chlorides as well as the presence and distribution of air voids. The main experimental variables are cement type and the quantity of silica powder, which varies from 0% to 25% of the cement weight. All mixes displayed negligible chloride ion penetration and high resistance to freeze-thaw with mass loss well below the limit in over 60 cycles of freeze-thaw. Analysis of the test data indicates that the silica powder content has little influence on performance.